Coping styles and personality type of Filipino women with intact and broken marriages. [article]. - Munez, Lucia Jemima O.
This study aims to compare the respondents' coping with the decision to either continue striving for marital commitment or to file a civil case brought about by the circumstances in marriage. Respondents' personality type is also considered in this study. Forty women in intact marriages and thirty-five in broken marriages in Quezon City were interviewed. Coping styles and personality types of women in both marriages were obtained from the ENRICH and MBTI scores. Significant differences revealed that: (1)conflict resolution and religion orientation were affected by age. (2)depending on profession, psychological types of judging,perceiving varied. under the coping styles, marital adaptability differed between two types of respondents. (3)as to intact or broken marriages, coping styles differed depending on length of marriage. In the context of an increasing number of petitioners for nullity of marriage and legal separation, this study responds to the growing need for strengthening the meaningfulness of Filipino marriages.